2017
DOI: 10.1002/ajh.24798
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter analysis of the use of transjugular intrahepatic portosystemic shunt for management of MPN‐associated portal hypertension

Abstract: BCR-ABL1-negative myeloproliferative neoplasms (MPNs) are clonal stem cell disorders defined by proliferation of one or more myeloid lineages, and carry an increased risk of vascular events and progression to myelofibrosis and leukemia. Portal hypertension (pHTN) occurs in 7–18% of MPN patients via both thrombotic and nonthrombotic mechanisms and portends a poor prognosis. Transjugular intrahepatic portosystemic shunt (TIPS) has been used in the management of MPN-associated pHTN; however, data on long-term out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…Laboratory tests mainly included liver, kidney and coagulation function. The study outcomes were the incidence of hepatic encephalopathy (HE) [24], variceal rebleeding, survival as well as shunt dysfunction which was defined as shunt thrombosis or stenosis resulting in clinical symptoms and/or requiring procedural intervention [25].…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory tests mainly included liver, kidney and coagulation function. The study outcomes were the incidence of hepatic encephalopathy (HE) [24], variceal rebleeding, survival as well as shunt dysfunction which was defined as shunt thrombosis or stenosis resulting in clinical symptoms and/or requiring procedural intervention [25].…”
Section: Methodsmentioning
confidence: 99%
“…52 In a retrospective study of 29 patients with MPN, TIPS was effective in resolving pHTN and its consequences, but 31% experienced in-stent thrombosis requiring additional interventions. 65 Finally, in patients with BCS with progressive liver dysfunction, transplantation may be required. 52 Among 78 patients with BCS who underwent liver transplantation, 41 had an MPN (40 with ET or PV) and had long-term survival comparable to that of those without MPN.…”
Section: Special Situationsmentioning
confidence: 99%
“… 7 Previous studies have shown that JAK2 V617 F has a prominent role in vascular risk and MPN-associated PHT. 8 , 9 The mechanisms underlying PHT in MPNs remain unclear. Splanchnic vein thrombosis (SVT) is a studied contributing force and extramedullary hematopoiesis within the liver and spleen also plays a pivotal role.…”
Section: Introductionmentioning
confidence: 99%